Luisa Paz RODRÍGUEZ SUÁREZ y José Ángel GARCÍA LANDA (Eds.) "Corporalidad, temporalidad, afectividad: perspectivas filosófico-antropológicas". Berlín: Logos, 2017, 305 pp. - Bueno Junquero, Adrián (Investigaciones Fenomenológicas, 2021)
-